The Acclimatization Stage Growth Of Black Orchid (Coelogyne Pandurata Lindl.) Plantlet By Biostimune Extract Gotu Kola (Centella Asiatica L.) Treatment - Hani Hani; Zulfa Zakiah; Mukarlina Mukarlina (LPPM UNIVERSITAS ISLAM KUANTAN SINGINGI, 2022)
Black orchid plantlets have a relatively slow growth at the acclimatization stage. The growth of black orchid plantlets can be increased by giving biostimulants. Biostimulants are bioactive compounds, and when they are applied, they can increase plant growth. This study aims to determine the effect of biostimulant Gotu kola extract (Centella Asiatica L.) on the growth of black orchid plantlets (Coelogyne Pandurata Lindl.) at the acclimatization stage. The research was conducted at the Biology Department's greenhouse from September until December 2020. The study used a completely randomized design with a factorial pattern. The first factor is the concentration of biostimulants consisting of 5 levels, e.g: 0 mg/L; 25 mg/L; 50 mg/L; 75 mg/L; 100 mg/L. The second factor is the application time which consists of 2 levels: once a week and once every two weeks. The results showed that the application of biostimulant Gotu kola extract had no significant effect on plantlet height, leaf length, leaf width, number of leaves, number of tillers, and number of plantlet roots of black orchid in the acclimatization stage.